2017
DOI: 10.14814/phy2.13236
|View full text |Cite
|
Sign up to set email alerts
|

Acute cardiac functional and mechanical responses to isometric exercise in prehypertensive males

Abstract: Isometric exercise (IE) training has been shown to reduce resting arterial blood pressure (ABP) in hypertensive, prehypertensive, and normotensive populations. However, the acute hemodynamic response of the heart to such exercise remains unclear. We therefore performed a comprehensive assessment of cardiac structure, function, and mechanics at rest and immediately post a single IE session in 26 male (age 44.8 ± 8.4 years) prehypertensive participants. Conventional echocardiography recorded standard and tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…[ 46 ] Furthermore, the magnitude of dBP response observed in the present study, which as indicated earlier might also be representative of previous IE interventions using the same standard protocol, may even act as a specific stimulus for the BP adaptations reported. Indeed, the physiological benefits following a single IE session including improved cardiac autonomic modulation and baroreceptor reflex sensitivity [ 30 ] and cardiac mechanical responses [ 47 ] have been recently reported. However, despite the potential importance of the dBP rise seen during IE, it is suggested that there will still be an adverse dBP threshold specifically pertinent to participants with suboptimal BP and as such a safe limit needs to be ascertained when prescribing this type of exercise in higher risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 ] Furthermore, the magnitude of dBP response observed in the present study, which as indicated earlier might also be representative of previous IE interventions using the same standard protocol, may even act as a specific stimulus for the BP adaptations reported. Indeed, the physiological benefits following a single IE session including improved cardiac autonomic modulation and baroreceptor reflex sensitivity [ 30 ] and cardiac mechanical responses [ 47 ] have been recently reported. However, despite the potential importance of the dBP rise seen during IE, it is suggested that there will still be an adverse dBP threshold specifically pertinent to participants with suboptimal BP and as such a safe limit needs to be ascertained when prescribing this type of exercise in higher risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…For the IET group, participants were required to complete a wall squat, consisting of resting their back against a fixed wall with their feet parallel, shoulder width aside, and their arms relaxed down by their side. As previously described (Goldring et al, 2014;O'Driscoll et al, 2017;Wiles et al, 2008), peak HR was determined via an incremental isometric wall squat test with beat-to-beat HR responses in accordance to the prescribed knee angle (Wiles et al, 2017). In line with previous evidence (Wiles et al, 2017), the intervention group was prescribed a 4-week IET program at a knee joint angle predicted to elicit 95% peak HR.…”
Section: Isometric Exercise Training Protocolmentioning
confidence: 99%
“…All images were examined to validate quality, and those that did not meet the required level of optimization and standardization were excluded. The sonographer's reproducibility of speckle-tracking indices have been previously reported (32). All echocardiography results were analyzed by an investigator blinded to participant order and condition.…”
Section: Study Population and Ethical Approvalmentioning
confidence: 99%